Synthesis of Bifluorenylidene- and Cycloocta[1,2,3-jk:6,5,4-j′k′]difluorene-Extended Tetrathiafulvalenes: Novel Multi-Redox Systems - Hansen, Jonathan Kirschner Solberg; Nielsen, Mogens Brøndsted (Synlett, 2024)
Herein, we present the synthesis of a novel 9,9′-bifluorenylidene-extended tetrathiafulvalene (TTF) as an E/Z isomeric mixture that was found to readily undergo an oxidative dimerization to furnish a TTF vinylogue with the two dithiafulvene units connected to an eight-membered ring fused to a bifluorenylidene core. This compound exhibited multiredox behavior and was found to take six charge states under cyclic voltammetry conditions: –2, –1, 0, +1, +2, +3. The dication corresponds to a cycloocta[1,2,3-jk:6,5,4-j′k′]difluorene with two appended 1,3-dithiolium rings.
Keywords: bifluorenylidene; C–C bond formation; chromophores; olefination; polycyclic aromatic hydrocarbons; tetrathiafulvalenes